2010
DOI: 10.1177/1352458510381258
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immune cell subsets during the active phase of multiple sclerosis reveals disease and c-Jun N-terminal kinase pathway biomarkers

Abstract: The analysis of the JNK-dependent apoptosis pathway can provide biomarkers for activated lymphocytes in the active phase of RRMS and a gene expression signature for disease status. The reported results might be useful to stratify patients, thereby supporting the development of novel therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…There are currently no commercially available JNK inhibitors, but a few oral JNK inhibitors, including CC‐930 (tanzisertib) and AS602801 (bentamapimod), recently entered clinical trials. CC‐930 is being tested in idiopathic pulmonary fibrosis and high‐dose CC‐930 caused elevation of hepatic transaminases when used for long‐term treatment .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no commercially available JNK inhibitors, but a few oral JNK inhibitors, including CC‐930 (tanzisertib) and AS602801 (bentamapimod), recently entered clinical trials. CC‐930 is being tested in idiopathic pulmonary fibrosis and high‐dose CC‐930 caused elevation of hepatic transaminases when used for long‐term treatment .…”
Section: Discussionmentioning
confidence: 99%
“…NUMB is a negative regulator of the Notch pathway and Notch plays an important role in T helper (Th) cell immune responses . It has been reported that NUMB is associated with the active phase of relapsing–remitting multiple sclerosis . STX3 is required for chemokine production by mature human mast cells, and altered STX3 expression and localization were found in salivary glands of patients with Sjögren's syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of both CD36 and ABCA1 are also upregulated in demyelinating spinal cord tissue from mice with EAE [88]. In addition, CD36 [122] and apoE [123,124] have recently been associated with the active phase of relapsingremitting MS.…”
Section: Discussionmentioning
confidence: 99%